2002
DOI: 10.1080/01639620290086468
|View full text |Cite
|
Sign up to set email alerts
|

gendered pathways into and experiences within crack cultures outside of the inner city

Abstract: This study examines the life histories of male and female crack addicts outside of the inner city context, focusing on gendered variation in experiences related to childhood background, pathways into crack cocaine use, income generation strategies, and violence. We offer insight into the nature of crack use and culture outside of the inner city and question the generalizability of previous studies to communities outside of the inner city. Furthermore, the question of women's emancipation and the subsequent imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…The narratives of the girls in our sample were reminiscent of research findings about gender relations among crack users (Evans et al, 2002;J. Miller, 1995).…”
Section: Resultsmentioning
confidence: 95%
“…The narratives of the girls in our sample were reminiscent of research findings about gender relations among crack users (Evans et al, 2002;J. Miller, 1995).…”
Section: Resultsmentioning
confidence: 95%
“…Non-injection drug use has been associated with HIV risk vulnerabilities in the context of sex work among women (Edwards, Halpern, & Wechsberg, 2006) and outside of this context (DeBeck et al, 2009). In particular, non-injection drug use has been linked to sexual risk behaviour and these experiences are situated within gendered power relationships that exacerbate risk (Evans, Forsyth, & Gauthier, 2002; Zierler & Krieger, 1997). Therefore, these findings suggest the importance of examining non-injection stimulant use within lesbian and bisexual intimate relationships to better understand unique HIV vulnerabilities of this population.…”
Section: Discussionmentioning
confidence: 99%
“…Female offenders have a high prevalence of drug abuse (Mumola & Karberg, 2006), which has been found to be strongly correlated with repeated involvement in the criminal justice system (Bloom et al, 2003a; Brennan, Breitenbach & Dieterich, 2010; Evans et al, 2002; Farabee, Joshi& Anglin, 2001; Sommers et al, 2000; Dunlap, Johnson & Maher, 1997; Mallik-Kane & Visher, 2008; McClellan et al, 1997). National statistics reported that 60 percent of women in State prisons and 43 percent of the women in Federal prisons met the criteria for drug dependence or abuse (Mumola & Karberg, 2006).…”
Section: Female Offender’s Drug Use and Victimizationmentioning
confidence: 99%